UMA SEQÜÊNCIA DE ENSINO USANDO O PROGRAMA WINPLOT: EM BUSCA DE UMA APRENDIZAGEM AUTÔNOMA DO ALUNO - Berleze, Caren Saccol (2007)
This research aims to analyze the Winplot contributions for the teaching and learning quality improvement of real functions, with focus on the graphical transformations. It also aims to analyze the interactivity influence (considering both the program and the classmates) in appearance of abilities, such as autonomy, criticality and creativity. The research was performed with 14 first-grade students from high school level at Colégio Militar de Santa Maria (CMSM). The used methodology followed some Didactic Engineering steps. We have elaborated a teaching sequence, based on 5 sessions, each one related to one type of real function (similar, quadratic, exponential, logarithmic and trigonometric). Each function-type was related to a practical situation involving the Earth Planet, associated with Geography and Physics. The preliminary studies had shown that the researched students have access to the computer; however, they use it basically for the leisure. On the other hand, the PCNs - Parâmetros Curriculares Nacionais, state that the student formation must contemplate the access to new technologies, in order to prepare him for the job market, which expects critical and independent citizens. For this reason, the classes must be more reflexive and participative, instead of simply informative. From the result analysis (proposed activities, reports, interviews, and comments) we have concluded that the work in pairs is important during the teach-learning process, since it generates environment for discussion, reflection and argument that develop the student criticality. In a short period of time, the use of Winplot made possible for the students to infer and prove their assertions, decreasing the dependence of the professor presence.